Human Melanoma-Associated Mast Cells Display a Distinct Transcriptional Signature Characterized by an Upregulation of the Complement Component 3 That Correlates With Poor Prognosis - Bahri, Rajia; Kiss, Orsolya; Prise, Ian; Garcia-Rodriguez, Karen M.; Atmoko, Haris; Martínez-Gómez, Julia M.; Levesque, Mitchell P.; Dummer, Reinhard; Smith, Michael P.; Wellbrock, Claudia; Bulfone-Paus, Silvia (Frontiers in Immunology, 2022)
Cutaneous melanoma is one the most aggressive human malignancies and shows increasing incidence. Mast cells (MCs), long-lived tissue resident cells that are particularly abundant in human skin where they regulate both innate and adaptive immunity, are associated with the melanoma stroma (MAMCs). Thus, MAMCs could impact on melanoma development, progression, and metastasis, by secreting proteases, pro-angiogenic factors, and both pro-inflammatory and immuno-inhibitory mediators. To interrogate the as yet poorly characterized role of human MAMCs, we have purified MCs from melanoma skin biopsies and performed RNA-seq analysis. Here we demonstrate that MAMCs display a unique transcriptome signature defined by the downregulation of the FcɛRI signalling pathway, a distinct expression pattern of proteases and pro-angiogenic factors and a profound upregulation of the complement component C3. Furthermore, in melanoma tissue we observe a significantly increased number of C3+MCs in stage IV melanoma. Moreover in patients, C3 expression significantly correlates with the MC-specific marker TPSAB1, and high expression of both markers is linked with poorer melanoma survival. In vitro, we show that melanoma cell supernatants and tumor microenvironment (TME) mediators such as TGF-β, IL-33, and IL-1β induce some of the changes found in MAMCs and significantly modulate C3 expression and activity in MCs. Taken together, these data suggest that melanoma-secreted cytokines such as TGF-β and IL-1β, contribute to the melanoma microenvironment by up-regulating C3 expression in MAMCs, thus inducing a MC phenotype switch that negatively impacts on melanoma prognosis.